Beyond Profit and Stress: Spirituality as a Bridge Between Business and Psychiatry in the Startup Era - Maulidatul Jinani Firdausyah; Nur Azizah; Hafid Algristian (Yayasan Sinergi Kawula Muda, 2026)
Micro and small-scale digital startups face intense psychological and operational pressures that often result in burnout, chronic stress, and adjustment problems. Yet, mental health issues within startup ecosystems remain insufficiently addressed and lack structured intervention. This literature review synthesizes cross-disciplinary studies published between 2013 and 2025 to examine how workplace spirituality can be integrated into startup work culture and its potential application within community psychiatry. The review indicates that workplace spirituality enhances mental well-being, reduces stress symptoms, and strengthens resilience, functioning as a psychological buffer for entrepreneurs facing high uncertainty. Spirituality also provides a conceptual bridge between managerial and clinical perspectives, enabling more holistic and human-centered approaches to mental health in startup environments. Integrating spiritual values into entrepreneurial settings emerges as an effective non-clinical strategy to sustain founders' mental health and expand opportunities for contextual community psychiatry interventions. The novelty of this study lies in its cross-disciplinary mapping that links startup management, spiritual psychology, and community psychiatry into a practical and preventive intervention framework.